Bugs and bones: a study of 25 cases of infectious spondylodiscitis - Sukumar, Cynthia A.; Rai, Shipra; Bhat, Shyamasunder N.; Saravu, Kavitha (International Journal of Advances in Medicine, 2021)
Background: Infectious spondylodiscitis (IS) is an illness that presents a diagnostic dilemma. It is often associated with significant neurological morbidity, hence early diagnosis and treatment is crucial. As only a few Indian studies have dealt with IS, our study analyses the unique clinico-epidemiological profile of this disease in India and assesses the current management trends and outcome in these patients. Methods: A retrospective study of 25 cases of microbiologically confirmed IS in a single unit at a tertiary care hospital over an 18-month period (January 2018 to June 2019). Results: A total of 25 cases of IS were considered with a mean age of 49 years. Among the cases of non-tubercular spondylodiscitis (NTS), the organisms isolated were methicillin-resistant Staphylococcus aureus (MRSA), Brucella, Escherichia coli and Citrobacter. The average time taken from onset of symptoms to diagnosis was 3 months in tubercular spondylodiscitis (TS) cases and 5 months in NTS cases. Neurological complications were seen in 32% of the patients. Magnetic resonance imaging (MRI) was the imaging modality used to confirm diagnosis in up to 80% of the patients. Medical and surgical management were required in 84% of the cases. Conclusions: The clinical conundrum in IS primarily due to its atypical presentation. The higher tubercular burden of IS was also confirmed in our study and the time taken to presentation was markedly longer compared to the western data. Therefore, understanding the clinical spectrum of this disease helps overcome hurdles of recurrence and debilitating neurological morbidity.